2011 IEEE Regional Symposium on Micro and Nano Electronics 2011
DOI: 10.1109/rsm.2011.6088336
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer graphene nanoribbon p-n junction

Abstract: Recently, one of the interesting topics in low dimensional condensed matter physics is p-n junctions. One of the applications of p-n junction is diode where this diode supply characteristics are applicable in both rectifiers and switching circuits. The discovery of p-n junction devices can ease the device design and investigation of physical events. Here we have reported the current in a single-layer graphene p-n junction in which carrier type and density in two adjacent regions are locally controlled by elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Using the plot, the slopes of the linear, fully transformed, regions of martensite (EM) and austenite (EA) material were calculated to be 30,000 and 40,000, respectively. The other required information, including Ms, Mf, As, Af, CM, and CA were taken from our previous studies and our readings of the literature, which were reported to be ࢤ65°C, ࢤ88°C, ࢤ23°C, ࢤ8°C, 5.7, and 8.6, respectively [ 42 , 43 , 44 , 45 , 46 ]. These material properties are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Using the plot, the slopes of the linear, fully transformed, regions of martensite (EM) and austenite (EA) material were calculated to be 30,000 and 40,000, respectively. The other required information, including Ms, Mf, As, Af, CM, and CA were taken from our previous studies and our readings of the literature, which were reported to be ࢤ65°C, ࢤ88°C, ࢤ23°C, ࢤ8°C, 5.7, and 8.6, respectively [ 42 , 43 , 44 , 45 , 46 ]. These material properties are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…[155][156][157] There has been much research interests in its photoelectron applications [158,159] and energy band structure of graphene under gate voltage. [160,161] However, electrical modulation requires additional biases and specialized processes and equipment, which limit the practical application of such graphene homogeneous pn junction.…”
Section: Electric Field Modulated Graphene Homogeneous P-n Junctionmentioning
confidence: 99%
“… 2 The purpose of mandibular reconstruction is to restore normal appearance, mastication, speech, swallowing, and breathing. 3 , 4 The most reliable means of restoring critical size or larger mandibular segmental defects is the use of a vascularized bone transfer, usually harvested from the fibula or iliac crest. 3 , 5 Typically, 1 or more surgical grade 5 (Ti–6Al–4V) 6 , 7 fixation devices are used to immobilize the graft.…”
mentioning
confidence: 99%